2017
DOI: 10.1542/peds.2016-4367
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Anorexia Nervosa: A Nationwide Study

Abstract: BACKGROUND AND OBJECTIVE: Previous research suggests an association of celiac disease (CD) with anorexia nervosa (AN), but data are mostly limited to case reports. We aimed to determine whether CD is associated with the diagnosis of AN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
65
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(74 citation statements)
references
References 29 publications
4
65
0
5
Order By: Relevance
“…It is worth considering screening for celiac disease with a total immunoglobulin A (IgA) and tissue transglutaminase IgA, as there is a high rate of co-occurrence of celiac disease and AN (16). Patients with bradycardia or hemodynamic instability should have an electrocardiogram.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth considering screening for celiac disease with a total immunoglobulin A (IgA) and tissue transglutaminase IgA, as there is a high rate of co-occurrence of celiac disease and AN (16). Patients with bradycardia or hemodynamic instability should have an electrocardiogram.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary restraint may induce counter‐regulatory responses, reduce sensitivity to satiety signals and result in disinhibited, binge‐like eating patterns. Evidence suggests that the increased focus on the content of food may inadvertently lead to other features of eating pathology …”
Section: Discussionmentioning
confidence: 99%
“…However, until recently, the relevant studies were mainly case reports and one population‐based study that included only hospital admitted CD patients, which might have amplified the reported risk. A recent nationwide study conducted in Sweden showed a positive bidirectional association between CD and anorexia nervosa …”
Section: Introductionmentioning
confidence: 99%
“…Planning and preparing food should not dominate thoughts and dictate behaviours above and beyond that of other daily activities . Recent research on disordered eating in CD indicates that both extreme GFD adherence and dietary transgressions are associated with disordered eating patterns . For those who fail to adhere to their GFD, the challenges of managing the GFD may lead to restrictive or bulimic eating behaviours .…”
Section: Introductionmentioning
confidence: 99%